From Politics as Vocation to Politics as Business: Populist Social Performance and Narrative Fusion in Trump Rallies. (22nd December 2021) - Karakaya, Yagmur; Edgell, Penny
Abstract: Populist movements seek to bolster the power of "the people" and undermine elites. In the United States a businessman, Donald Trump, has convinced a significant portion of the population that he is a man of the people. We answer three inter-related questions about what may be Trump's biggest "win": the transformation of populist discourse for a new century. How does Trump embed himself inside his followers' own deep story? How does he fuse their story with a tale of American restoration? And how does he delegitimize politics as a vocation and valorize politics as business? Drawing on a systematic analysis of Trump/MAGA rallies held in four different regions from 2015 to 2021, we analyze how Trump used his performance to crystalize a distinctly American style of populism. We focus on the cultural accomplishment of his performance, particularly the creation of a business-friendly rhetoric that leverages popular cultural idioms to legitimate politics not as a vocation, but as a business. We find that Trump uses the popular idioms of standup comedy and competitive sports culture. This performance contributed to his 2016 win, yet framing politics as a game to be won runs the risk of reducing deliberative democratic process to election-night outcomes, makes political parties into opposing teams, and divides voters into winners and losers.